Comparison of Ovarian and Cervical Cancer Prevalence in Iraqi Women with Lowered Serum Antioxidant Levels - Abdulla, Kawakeb N; Findakly, Sura Basil; Majeed, Asmaa Taha; Mahdi, Montadher Ali; Biden, Bidaa (Journal of Contemporary Medical Sciences, 2025)
Objective: This study aimed to assess the correlation between a decline in serum endogenous enzymatic antioxidant levels and cervical and ovarian cancer incidence and to determine which type of cancer was more significantly influenced by the decrease in endogenous enzymatic antioxidants among Iraqi patients. Methods: it’s a retrospective study comprising a total of 100 adult females, including 50 patients with ovarian and cervical cancer, recruited from the Oncology Teaching Hospital in Baghdad, Iraq, between January and March 2024. The patient's history was acquired with the patient's consent. Biochemical tests were performed using a spectrophotometric technique to estimate serum endogenous enzymatic antioxidant levels, including catalase, superoxide dismutase, and glutathione peroxidase. Results: The study demonstrated a significantly lower serum level of catalase, superoxide dismutase, and glutathione peroxidase among the study population with cancer compared with healthy women. Among the positive cases, The number of patients with cervical cancer was significantly higher than that of those with ovarian cancer. Further, the level of endogenous enzymatic antioxidants in patients with cervical cancer was lower than that in patients with ovarian cancer. Conclusion: The findings of this study indicate that the serum level of endogenous enzymatic antioxidants may serve as a marker for predicting the incidence of cervical cancer, particularly associated with human papillomavirus infection, with a lesser association with ovarian cancer.